Critical Dialogue: Navigating Internationalization and Invisible International Students in Canadian Higher Education - Eden, Cynthia; Kang, Phoebe (Journal of Teaching and Learning, 2026)
This critical dialogue employed critical multiculturalism and critical internationalization as overarching theoretical frameworks and uncovered continuous and ongoing struggles for invisible international students and racialized nonnative English-speaking educators in English for Academic Purposes programs in the Canadian Higher Education context. Utilizing duo-ethnographic method, the two EAP educators’ dialogues uncover ongoing struggles in English language education in English-speaking countries, specifically in Canada including native and nonnative English speaker dichotomy in English language teaching and learning, deficit mindset, racial microaggressions, and the lack of institutional and systemic supports for the invisible international English language learners (ELLs). We are calling for policy and institutional action to support all international students in creating truly inclusive teaching and learning environments.